Ungkapan Kepercayaan Rakyat di Kenagarian Tapan Kabupaten Pesisir Selatan - Alfianto, Alfianto; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purposes of this research are: (1) describing the category of someone’s idiom faith in Tapan, Basa Ampek Balai subdictrict, Pesisir Selatan regency. (2) Describing about the meaning of someone’s idiom faith in Tapan, Basa Angkek Balai subdictrict, Pesisr Selatan regency. (3)describing the function of someone’s idiom faith in Tapan, Basa Angkek subdictrict, Pesisir Selatan regency. In this research consist of the data about the idiom of someone’s faith in Tapan, Basa Angkek Balai subdictrict, Pesisr Selatan regency. The data has been collected by listening method, interviewing, recording and written technique.  The founding of this research is the highest category of someone’s idiom faith is about rumah category and rumah tangga job. (2) The meaning of someone’s idiom faith in Tapan belongs to analogy and direct speech.(3) the function of someone’s idiom faith in Tapan is to educate and build someone’s faith and religion. The category that has in Tapan is not only about human but also the animal adventure, plants, and others things that someone’s beliefs or magic.